Paciente femenino de 30 años de edad diagnosticado con astenopia y alteración visual. - Sánchez Parrales, Julio Arturo (2020)
Witin the study of this clinical case, the importance is highlighted because the visual alteration (Asthenopia) causes a series of problems due to daily activities such as watching television, driving, insufficient light conditions, medication, refractive errors, lack of sleep, or due to environmental causes, in addition to the refractive visual alteration that the patient presents such as myopia, there are signs such as frowning, getting too close to read or write, turning or tilting the head, and symptoms such as headache, dizziness and some pain around the eyes all this is detrimental to the patient's eye health, it is for this reason that the objective of this clinical case is set to identify the cause of fatigue and visual alteration of the patient in both eyes, and for this objective, subjective and complementary examinations were carried out, as well as the different tests; Bruckner reflex, Hirschberg test, Worth light test, Ishihara test, But test, Schirmer test, to collect the information the inductive method was used, which will serve as a premise to propose a logical reasoning of the case under study. Bibliographic data was used and they were contrasted with the real data provided by the patient under study, as a result it was found that the patient suffered from headache, burning, tearing and redness of the eyes, especially when performing the study tasks with electronic devices such as the computer or the cell phone by not using lenses with protection filters for this equipment, after a careful study of the Optometric examinations it is concluded that the visual defect of the patient is a myopia as a refractive defect and eye fatigue due to stress.